Other Spaces in Legal Pedagogy - 余江 (2004)
There is an increasing focus upon the material and metaphoric spatial dimensions of various academic disciplines, including law. This essay considers the spatial dimensions of legal pedagogy, focusing on Critical Race Theory (CRT). The essay first explains the critical program in law and how CRT grows out of it. The essay then suggests that the critical program, and especially CRT, is as much a human geographic or spatial construct as it is a social, political or historic one, and briefly describes the nature of human geography and legal geography. It next considers how metaphors for understanding CRT's position in legal pedagogy are found in some of Foucault's work on geography. In Des Espaces Autres ( Other Spaces ), Foucault argues that there are three distinct social spaces in society: real spaces, utopias, and heterotopias. What unites them, Foucault suggests, is a space that includes elements of all of these spaces, a space that he calls the mirror. Applying this frame, this essay posits that CRT, both the explicit courses on the topic and the discipline itself, should be re-mapped , that is, barriers to its inclusion in the broader legal pedagogy should be eliminated. In this way, CRT can function as a Foucauldian mirror rather than a heterotopia in legal pedagogy